ANALISIS PERBANDINGAN KINERJA KEUANGAN BPR MILIK PEMERINTAH DAERAH DENGAN BPR MILIK SWASTA DI PROVINSI BALI PERIODE 2019-2021 - Ni Putu Sinta Kharisma Dewi; Yudantara, I Gede Agus Pertama (Vokasi : Jurnal Riset Akuntansi, 2022)
This research aims to compare the financial performance between Regional Government-Owned BPRs and Private BPRs in terms of the various financial ratios listed in POJK Number 48/POJK.03/2017 concerning Transparency of Rural Bank Financial Conditions. The type of research used is quantitative research with a comparative descriptive research design. The data analysis method used in this research is Independent Sample T-Test or Mann Whitney U which is adjusted to meet the requirements of normality and homogeneity which is processed with the help of the SPSS 26.0 for Windows data processing program. The results of this study are that there are differences in financial performance between Regional Government Owned BPRs and Private BPRs in terms of LDR and CR ratios, while from other ratios such as KPMM, PPAP, NPL, ROA, and BOPO ratios there is no difference in financial performance between Regional Government Owned BPRs. with Private Owned BPR.